THE EFFECTIVENESS OF THE TALKING STICK-ASSISTED PROBLEM-BASED LEARNING MODEL ON SELF-EFFICACY AND MATHEMATICAL CONTEXTUAL PROBLEM-SOLVING SKILLS - Syafira, Aulia; Isnani, Isnani; Munadi, Munadi (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
The aim of this study was to determine the effectiveness of the Talking Stick Assisted Problem Based Learning learning model in the subject matter of Data Presentation on Self Efficacy and Contextual Mathematical Problem Solving Ability for class VII students of SMPN 19 Tegal City. This research is a quantitative research. The population used in this study were all class VII students of SMP N 19 Tegal City for the 2022/2023 Academic Year. The sample used is using purposive sampling. Data collection techniques using tests and questionnaires. From the results of the study it was found that the Self Efficacy of students who were taught using the Talking Stick Assisted PBL model was better than those taught using the Conventional model and obtained an increase before and after treatment in the moderate category. For mathematical contextual problem solving abilities, the results of students' solving abilities taught using the Talking Stick Assisted PBL model were better than those taught using the Conventional model and the value of mathematical contextual problem solving abilities taught using the Talking Stick Assisted PBL model reached KKM.